Cultural connections franco-portuguese-brazilian: memory and representation in the media training in Brazil - Oliveira, Aline Cristina de [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2015)
With the arrival of the Portuguese royal family in Brazil in 1808, the cultural, existing transfers since colonization, became more constant and intense. This was due to two major measures engendered by D. Joao IV: the opening of ports and the implementation of the press. In spite of the efforts to the establishment of a press that reproduce the one made in Portugal, which was observed was a latent participation of France that manifested socio-culturally in Brazil since the reestablishment of cordial relations in 1816 and thus was also showed present in journalism. From independence, the Luso-Brazilian relations were quite shaken and francophilia was imposed in forming the new nation-state. The Brazilian press, which was constituted on the basis of the Franco-Lusitanian influx, culturally connecting the three countries, a fact that undermines the notion of cultural transfers as a Eurocentric movement and reinforces the idea that the recent changes were bilateral or even multilateral.
Keywords: Cultural connections; Press; XIX century; Brazil; Portugal; France